ANALYZING TIKTOK’S INFLUENCE ON YOUTH POLITICAL ACTIVISM AND SOCIAL PARTICIPATION IN MALAYSIA - Mohd Nor, Nor Azyani Tsania; Mohd Fird, Syahirah Samantha Foo Su Sien; Nabilah Mohd Ridhwan, Nur Marissa; Hafifi Jamri, Mohamad; Azmi, Mohammad Fazrulzaman (Universitas Padjadjaran, 2025)
Despite TikTok’s popularity among young users, concerns persist regarding their lack of political awareness and gullibility. This research aims to address this gap by examining TikTok usage patterns among Malaysian youth and analyzing user interactions with political and social content. The research participants consisted of youths aged 18 to 29 years old in Malaysia. Employing a quantitative research design, the study used surveys to gather data and descriptive statistical analysis. The collected data was analyzed using the SPSS software. The study’s findings indicate TikTok’s potential for political usage and respondents show a moderately high agreement on TikTok as a platform to increase political awareness. Theoretical framework of Agenda-setting Theory guides the analysis of user interactions to uncover mechanisms of influence and information dissemination. By providing insights into how TikTok influences political discourse and shapes youth engagement, this research contributes to understanding social media’s role in civic participation.